Clinical pharmacology during pregnancy and lactation - Allegaert, Karel (Henry Stewart Talks, 2024)
Clinical pharmacology during pregnancy and lactation, Pharmacokinetics and pharmacodynamics during pregnancy, Pregnancy-related physiological changes, Placenta-related drug transfer, Lactation-related drug transfer, Guidance and practices